Impact of Coronavirus Disease 2019 on the Incidence of No Prenatal Care - Tanamoto, Takaki; Hayasaka, Misa; Robbins, Lindsay; Saade, George; Kawakita, Tetsuya (American Journal of Perinatology, 2025)
This study aimed to examine the impact of coronavirus disease 2019 (COVID-19) on the racial disparity in prenatal care utilization in the United States before and during the pandemic.This was a cross-sectional study using the National Vital Statistics Data from 2018 to 2022. Our focus was on low-risk individuals who delivered singleton pregnancies at term. The analysis was restricted to Black and White individuals to explore racial disparities. The study periods based on the last menstrual period (LMP) were prepandemic (March 2018–February 2020) and pandemic (March 2020–February 2022). The primary outcome was the rate of no prenatal care. We employed interrupted time series analysis, negative binomial regression models, adjusting for confounders, seasonality, and autocorrelation. We conducted postestimation analyses to calculate the counterfactual and actual incidences of outcomes for individuals with an LMP in March 2020 and February 2022. Difference-in-difference (DID) with 95% confidence intervals (95% CI) was estimated.The analysis included 3,511,813 individuals in the prepandemic period and 5,163,486 in the pandemic period. For individuals with LMP in March 2020, the actual incidences of no prenatal care per 100 births were 3.2 (95% CI: 3.0, 3.3) for Black individuals and 1.6 (95% CI: 1.2, 2.0) for White individuals. The difference between counterfactual and actual no prenatal care rates per 100 births for Black individuals was 0.4 (95% CI: 0.2, 0.5), indicating a significant increase in no prenatal care. Conversely, there was no significant difference for White individuals. DID analysis further demonstrated that this increase was greater in Black individuals compared with White individuals (DID per 100 births 0.3 [95% CI: 0.1, 0.5]). For individuals with LMP in February 2022, this difference in disparity further worsened (DID per 100 births 0.8 [95% CI: 0.4, 1.2]).The COVID-19 pandemic increased the incidence of no prenatal care, which disproportionately affected Black individuals.
Keywords: coronavirus disease 2019; APNCU index; no prenatal care; Black; pandemic